Massive blood loss in surgery for renal cell carcinoma associated with inferior vena cava tumor thrombus: Observational study - Pavel I. Feoktistov; Alexandr R. Shin; Alexey O. Prikhodchenko; Evgeniya N. Feoktistova; Pavel V. Vyatkin (ZAO "Consilium Medicum", 2022)
Background. An effective treatment for renal cell carcinoma complicated by tumor thrombus (TT) is nephrectomy with thrombectomy (NETE) from the inferior vena cava (IVC), which is associated with massive blood loss, high morbidity and mortality. The study aims to evaluate the infusion-transfusion protocol (ITP) for NETE from the IVC without extracorporeal circulation. Materials and methods. The observational single-center study included 682 patients who were operated for NETE for renal cell carcinoma with TT. Patients were divided into 3 groups depending on the level of TT according to the Mayo classification. The InfraHepatic (InH) group included patients with TT levels I and II, the RetroHepatic (RH) group included patients with TT level III, and the SupraDiaphragmatic (SD) group included patients with TT level IV. Own concept of moderately advanced infusion in the amount of 130140% of all losses were introduced. Qualitative and quantitative composition of ITP, frequency of use of sympathomimetics, complications and mortality were assessed. Results. The rate of massive blood loss was 46.9% in the InH group, 74.7% in the RH group, and 86.3% in the SD group. ITP was characterized a significant increase in the absolute values of all infusion media, a decrease the proportion of crystalloids and colloids, an increase the proportion fresh frozen plasma, donated erythrocytes, and proportion of auto-erythrocytes between groups. The frequency of using intraoperative cell salvage in the InH group was 39.6%, in the RH 67.7%, in the SD 90.7%. The greatest hemodynamic shifts were recorded in the SD group. The frequency of postoperative complications was 24.3%, and hospital mortality was 7% with accordance to the ITP, adequate hemodynamic and laboratory monitoring in NETE. Low mortality due to hemorrhagic shock in our study (0.15%) emphasizes the effectiveness of the presented ITP. Conclusion. The obtained data demonstrate the results of NETE as comparable with those presented in the available literature.